"Jasper Jones" as a Window into Australia’s Aboriginal history (NEW: Emerging scholars in Australian Indigenous Studies, 2020)
Jasper Jones (2017) is an Australian film adaptation of Craig Silvey’s 2009 novel of the same name. The film is directed by Arrernte woman Rachel Perkins, who founded Blackfella Films in 1992 and has since been heading the initiative to include more Indigenous representation on screen. With an Aboriginal character, Jasper Jones, at the forefront of the story, the film presents a window into the lives of Aboriginal people living in 1960’s white Australia.